مستوى الإبداع الإداري والقيادة لدى مديري المدارس الإبتدائية من وجهة نظر مديري ومعلمي إدارة الحسينية التعليمية محافظة الشرقية - مرعي، على عبدالرحمن محمد; الشناوي، الشناوي عبدالمنعم Alshennawi, Alshennawi Abdulmoneim; موسى، فاتن فاروق عبدالفتاح; فرير، فاطمة حلمي حسن (جامعة بورسعيد - كلية التربية, 2014)
يهدف هذا البحث إلى التعرف على مدى توافر الإبداع الإداري والقيادة، كذلك فهم عملية الإبداع في الإدارة المدرسية ومدى ارتباطها بالقيادة لدى مديري المدارس الابتدائية. وتحديد الفروق في مستوى الإبداع الإداري والقيادة لدى مديري المدارس الابتدائية بإدارة الحسينية التعليمية-محافظة الشرقية-تبعاً لمتغيري (النوع-الوظيفة). ولهذه الأغراض تم تطبيق مقياسي الإبداع الإداري (عبد الرحمن محمد جبر) والقيادة (فاروق عبد الفتاح موسي) بعد التحقق من ثباتهما وصدقهما. وتكونت عينة البحث من (160) فرداً عبارة عن (140) معلماً ومعلمة و(20) مدير ومديرة مدرسة. وأظهرت نتائج البحث ارتفاع مستوى الإبداع الإداري لدي مديري المدارس الابتدائية من وجهة نظر كل من المعلمين والمديرين أنفسهم. كما أظهرت نتائج اختبار (ت) عدم وجود فروق في مستويات الإبداع الإداري لدى مديري المدارس الابتدائية بإدارة الحسينية التعليمية محافظة الشرقية ترجع إلى متغير النوع (ذكور/ إناث). كذلك عدم وجود فروق في مستويات الإبداع الإداري والقيادة الإشرافية لدى مديري المدارس الابتدائية بإدارة الحسينية التعليمية محافظة الشرقية ترجع إلى متغير الوظيفة (مدير/ معلم)، باستثناء بعد واحد في الإبداع الإداري (الانفتاح على التغيير)، وبعد واحد في القيادة الإشرافية (البنية). كما أظهرت معاملات ارتباط بيرسون وجود ارتباط بين مستوى الإبداع الإداري والقيادة لدى مديري المدارس الابتدائية بإدارة الحسينية التعليمية محافظة الشرقية، من وجهة نظر كل من المديرين والمعلمين. وفى ضوء نتائج البحث وتفسيرها ومناقشتها تم اقتراح مجموعة من التوصيات ومنها ضرورة تدريب المعلمين ومديري المدارس على مهارت القيادة كذلك توفير الظروف البيئية الملائمة لممارسة الإبداع الإداري داخل المؤسسات التعليمية حتى ينعكس أثره الإيجابي على العملية التعليمية بشكل عام. This research aims to identify the availability of Administrative Innovation and Leadership, as well as understanding the process of innovation in school management and its relation with leadership of primary school directors. And to identify the differences in the level of Administrative Innovation and administrative leadership of primary school directors Husseiniya educational Directorate–Sharkia Governoratedepending on variables (Gender - Occupation). For these purposes the researcher applied the Administrative Innovation Scale (Abdul Rahman Mohammed Gabr) and leadership Scale (Farouk Abdel-Fattah Musa) after verification of their stability and Validity. The sample consisted of (160) individuals as (140) teachers and (20) Directors of Primary Schools. The results of the search show high level of Administrative Innovation for Primary school directors from the point of view of both teachers and directors themselves. The results of (T) test show no differences in the levels of Administrative innovation for primary school directors at Husseiniya Educational Directorate, Sharkia Governorate, due to Gender variable (male / female). As well as the lack of differences in the levels of Administrative Innovation and Administrative leadership for directors of primary schools at Husseiniya educational Directorate – Sharkia Governorate- due to the variable function (Director / Teacher ) , with the exception of one dimension in creativity administrative (openness to change) , and after the one in command supervisory (Structure ). It also showed correlation coefficients (Pearson correlation) between the level of Innovation and Administrative leadership for primary school directors in the management of Husseiniya educational Eastern province , from the point of view of both directors and teachers According to the results of research, interpretation and discussion a series of recommendations has been proposed, including the need to train teachers and directors on the Skills of leadership as well as providing appropriate environmental conditions for he training on Administrative Innovation in educational institutions so that it can reflected a positive impact on the educational process in general.
Keywords: السياسة التعليمية -- البرامج التعليمية -- الوسائل التعليمية -- علم النفس التربوي -- التعليم الإبتدائي -- طلاب المرحلة الإبتدائية